Crenças e atitudes das populações chave acerca da profilaxia pré-exposição ao HIV/AIDS - Batista, Amanda Trajano (2021)
By proposing a preventive method based on the use of antiretrovirals (Arvs), Pre-exposure prophylaxis (Prep) has had an impact on HIV prevention, raising concern about how users can change their sexual and preventive behaviors. Based on the Theory of Rational Action and the Model of Vulnerability and Human Rights, this thesis is based on the assumption that Prep is a dynamic phenomenon, being more than a biomedical and pharmacological intervention, by incorporating psychological and social aspects that, together, they affect people’s vulnerability to the prevention of HIV infection and other STI, as well as the dynamics of sexual relationships and practices. Thus, four studies were developed. Study 1: To analyze the sexual and preventive practices of the so-called key populations before and after the use of Prep, regarding the incidence of STI, number of sexual partners and condom use. Method: This is an exploratory, cross-sectional and documentary study, in which 100 medical records of patients using Prep were analyzed. The data were analyzed using descriptive statistics (Frequency, Mean, Standard deviation). Results: Most of the sample was composed of men who had sex with men-MSM (56%), followed by people in a different serum-DS partnership (36%), with an average of 33 years, and complete high school (39%) or higher education (37%). Regarding sexual practices, the data demonstrate that between MSM and DS there was a decrease in condom use, an increase in STI, and an increase in sexual partnerships between MSM after three months of Prep use. Such data show an increase, albeit a slight one, of the sexual practices considered at risk in the population prioritized for the use of Prep, as well as a decrease in preventive practices related to condom use. Study 2: aimed to analyze behavioral beliefs regarding the advantages and disadvantages of using Prep. Method: The sample was composed of 31 participants from four key populations, who are already using Prep. Participants were contacted online. As a collection instrument, a questionnaire based on the Theory of Rational Action was used, composed of four open questions, in addition to sociodemographic data. Quantitative data were analyzed by descriptive statistics, while qualitative data were analyzed by thematic categorical analysis. Results: Regarding the advantages of using Prep, 84 beliefs were obtained, the main ones being: 1) Double protection, 2) No condom use, 3) Decrease contamination, 4) Decrease Stis, 5) Autonomy in prevention. Regarding the disadvantages, 95 beliefs were obtained: 1) Side effects, 2) Ineffectiveness, 3) Non-use of condoms, 4) Focus on HIV, 5) Ingest daily. Study 3: It aimed to build an instrument aimed at measuring the attitudes of users of Pre-exposure-Prep Prophylaxis regarding condom use, gathering evidence of its factorial validity and internal consistency, following the assumptions of the Rational Action Theory (TAR). Method: This is a psychometric and methodological study that included a sample of 178 subjects from the three key priority populations for the use of Prep, namely: men who have sex with men (MSM), sex workers and people who have different serum partners. Results: The instrument was composed of 26 items, which included aspects related to the TAR constructs, each type inserted in a subscale, whose variables were evaluated from a bipolar scale of the Likert type, ranging from 1 to 5 (with mean point equal to 3) discriminating groups with Negative Intention (1 to 2) and Positive Intention (4 and 5) in performing the behavior. The exploratory analyses indicated three factors related to the structure of ART, presenting a good internal consistency and reliability represented by the Crobrach’s Alpha coefficient: Direct Attitude Measurement (45.2% of explained variance and Alpha 0.74); Indirect Attitude Measurement (30.8% of explained variance and Alpha 0.48); Indirect Subjective Norm Measurement (58.2% of explained variance and Alpha 0.63). Study 4: sought to investigate the behavioral intention of three key populations regarding condom use in Prep use, assessing the association of socio-demographic variables on the behavioral intention of the participants. Method: This is a quantitative study, of descriptive and correlational nature, with the same sample of the previous study. The Attitudes Scale to Pre-exposure HIV Prophylaxis was used as an instrument, as well as a sociodemographic questionnaire. For the data analyses, descriptive and bivariate and inferential statistics were performed (Chi-square, Pearson correlation and multiple regression). Results: Behavioral beliefs and direct attitudes significantly predict behavioral intent, suggesting that, in the key populations studied, behavioral beliefs are the main predictors of the intention of users of Pre-exposure Prophylaxis (Prep) in using the condom, with contribution of normative beliefs in the explanation of variance. However, it is observed that the stronger the beliefs, the less the intention of the joint use of Prep and condom. The MSM group presented a positive intention to use combined prevention, unlike people in different Serum partnerships and Sex Professionals who have a negative intention to use Prep and condoms. The analyses showed a positive correlation between schooling and intention, showing that the higher the level of education, the more positive is the intention to use Prep and condoms. However, no significant correlations were found between intention and age and intention and income. The results showed that, in general, the longer the time of use of Prep, the lower the use of condoms. Among the specific key populations, MSM and Sorodiferentes who have been using Prep for more than six months presented lower condom use, as opposed to participants in Sorodiferentes partnerships where condom use is higher among those who have been using Prep for less than 6 months, while among those who never use condoms, they have been doing so for more than six months. The association between condom use and time using Prep was not significant among female sex workers. Conclusion: Taken together, the four studies enabled the identification of factors that can positively or negatively influence the adoption of preventive behavior, which may subsidize the protocols of care and public health policies.